Optimalisasi Pemanfaatan Koleksi Sastra melalui Digitasi dan E-Service untuk Mendukung Pembentukan Karakter Bangsa: Studi Kasus pada 6 Perpustakaan Anggota FPPTI-DIY yang Perguruan Tingginya Memiliki Program Studi Sastra - Fransisca Rahayuningsih; MM. Hastutiningrum (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2020)
One of the ways to shape the dignity of a nation is to broaden the horizons of language and culture and this can be done by reading literary collections. The role of literature, of course, cannot be explained by physical evidence because literature talks about the soul, the spirit, and something related to one's mind. However, if disseminated to the public, literary works can produce future generations who are more competent, critical, creative, and most importantly, have a conscience. Literature plays a role in shaping the character of a nation. This study aims to determine how the literature books in the 6 FPPTI-DIY member libraries are used by users. This research is also intended to determine whether the use of literary books has an effect on character education? In addition, this research is also intended to provide recommendations in order to optimize the use of literary books through digitization and e-service. The research design was designed using mixed methods. The strategy used in this research is sequential explanatory strategy. The population in this study were library visitors of FPPTI DIY members from 6 universities with 617,539 literature study programs. Sampling was done by using the stratified sampling technique. Qualitative data collection was determined by looking at gender and literature reading preferences. There were 4 people assigned from each library, consisting of 2 male visitors who like to read and 2 female visitors who don't like to read, as many as 24 informants. Data analysis was performed using SPSS for Windows version 21. The results of this study prove that the use of literary books in 6 FPPTI-DIY member libraries, those literary books are used by users when there are lectures related to literature. This was conveyed by respondents with a frequency of coming 1-2 times a week and a frequency of utilizing literary collections twice a week. Through the results of quantitative analysis by testing the hypothesis of this study proves that the quality, quantity, and visibility of books have an effect on optimizing the use of literary books through digitization and e-service on character building. The role of 6 FPPTI-DIY member libraries in optimizing the use of literary books, which is related to the importance of reading literature through digitizing literary collections and e-service is considered good enough and overcomes the limitations of book availability.